ANALISIS KINERJA BANK DAERAH SEBELUM DAN SETELAH PENERAPAN OTONOMI DAERAH - Suparwati, Yohana Kus (PRESTASI, 2009)
Legalized in Act No.32 2004 about Regional Government and Act No.33 2004 about balance of finance between regional government and central governmentÂ  impact an important implication to regional economic supported by Regional Bank. This study purposed to analyze the influence of regional authority implementation to regional bank performance. Sample used in this research is report of finance before and after implementation of regional authority by using performance indicator based on CAMEL and evaluated by Wilcoxon Signed Rank Test. The result showed that there were no significantly different before and after the implementation of regional authority to regional bank performance, however in general showed that the performance of regional bank increased.